The Lifting Performance and Experimental Study of a Variable Spiral Spike-Toothed Crop Divider - Jing Bai; Shaochun Ma; Chao Cheng (Agriculture, 2024)
The contact between a traditional crop divider and sugarcane is unstable, and the sugarcane easily slides off of its surface. By analyzing the movement process of sugarcane, the influence of traditional spiral flightings on lifting performance was studied, and shortcomings were also found. Based on previous research and analysis, the variable spiral spike-toothed crop divider was designed by research groups. For sugarcane with different lodging states, the contact separation rule between the sugarcane and the spike tooth was studied, and the action time and angle of the spike tooth on sugarcane were obtained. At the same time, the interaction mechanism between sugarcane and the spike tooth was analyzed, and the conditions for lodged canes to be lifted were obtained. The influence of the spike tooth on the lifting performance was explored, and the working advantages were found for the spike-toothed crop divider. Then, a simulation test was conducted to obtain the contact force between the sugarcane and the crop divider. Finally, the crop divider was optimized and integrated into the harvester, and a field harvesting test was carried out to verify the working performance of the crop divider. This study was expected to provide a reference for the design of crop dividers and a theoretical basis for the analysis of the lifting process.